Race as a moderator in the relationship between trauma exposure and resilience among South African adolescents - Stone, La-Toya (University of the Free State, 2015)
Resilience and trauma exposure are well researched topics. There is extensive knowledge about the nature of traumatic events that adolescents are exposed to, as well as how they have coped with these experiences. The role of race in the relationship between these two variables is not extensively researched and little is known about the exact influences it could or could not have on resilience. With South Africa’s tainted past and the aftermath of the apartheid era, it is difficult to separate racial influences in both resilience and trauma exposure. In turn, race can seldom be separated from culture, and this has further influences on how individuals execute certain tasks or relate to situations. Racial influence is therefore an important area to research if differences in resilience exist among South African citizens, and especially adolescents. The results obtained from this study can therefore be used to add a new perspective to an already rich literature on resilience. The aim of the study was to investigate the moderating influence of racial membership in trauma exposure and resilience among 862 South African adolescents. A non-experimental correlational design was used to describe the relationship between the variables. Correlational studies were further used to determine the extent to which the variables were related. The measuring instruments consisted of a biographical questionnaire, a shortened version of the Stressful Life Events Questionnaire (SLESQ) and the Resiliency Scales for Children and Adolescents (RSCA). The role of racial membership in the relationship between trauma exposure and resilience was investigated using a moderated hierarchical regression analysis. Results from the study indicated that race did not exert a statistically significant moderator effect in the relationship between trauma exposure and resilience among adolescents. The interaction term was therefore dropped from the model and further investigation revealed that there was a statistically significant relationship between race and resilience, after the effects of trauma exposure were taken into account. The white participants in the study had statistically significantly higher levels of resilience compared to the black participants.

Veerkragtigheid en blootstelling aan trauma is onderwerpe wat al breedvoerig nagevors is. Daar is baie ingligting oor die natuur van trauma, die tipe traumatiese blootstelling wat adolessente ervaar, asook hoe adolessente hierdie trauma hanteer. Die rol van ras in die verhouding tussen hierdie twee veranderlikes is nie omvattend nagevors nie en daar is min bekend oor die presiese invloed wat dit kan hê op veerkragtigheid. Met Suid-Afrika se besmette geskiedenis en die nagevolge van die apartheids era, is dit moeilik om rasse invloed te skei in beide veerkragtigheid en blootstelling aan trauma. Op sy beurt, kan ras selde geskei word van kultuur, en dit het verdere invloed op hoe individue sekere take uitvoer of verband hou met situasies. Rasse invloed is dus ‘n belangrike gebied vir navorsing, indien die verskille in veerkragtigheid vlakke bestaan onder Suid-Afrikaners, en veral adolessente. Die studie resultate kan dus gebruik word om ‘n nuwe perspektief te voeg tot ‘n reeds ryk literatuur oor veerkragtigheid. Die rol van hierdie studie was om die matigende invloed van rasse lidmaatskap in trauma blootstelling en veerkragtigheid onder 862 Suid-Afrikaanse adolessente te ondersoek. ’n Kwantitatiewe, nie-eksperimentele, korrelasionele ontwerp is gebruik in hierdie studie om die verhouding tussen die veranderlikes te beskryf. Die meetinstrumente bestaan uit 'n biografiese vraelys, ‘n verkorte weergawe van die ‘Stressful Life Events Questionnaire (SLESQ)’ en die ‘Resiliency Scales for Children and Adolescents (RSCA)’. Die rol van rasse lidmaatskap in die verhouding tussen trauma blootstelling en veerkragtigheid is ondersoek deur gebruik te maak van 'n hiërargiese regressie-analise. Resultate van die studie dui daarop dat ras nie ‘n statistiese beduidende effek speel in die verhouding tussen trauma blootstelling en veerkragtigheid onder adolessente nie. Die interaksie term is dus gedaal van die model en daar is verdere ondersoek aan die lig gebring dat daar ‘n statistiese beduidende verband tussen ras en veerkragtigheid is, na die gevolge van blootstelling aan trauma in ag geneem is. Die blanke deelnemers in die studie het statisties beduidend hoёr vlakke van veerkragtigheid in vergelyking met die swart deelnemers getoon.
Dissertation (M.A. (Psychology))--University of the Free State, 2015
Keywords: Resilience; Trauma exposure; Adolescents; Race; Culture; Apartheid era; South Africa; Moderating influence; Relationship; Participants; Teenagers -- South Africa